Relationship between serum inflammatory cytokines and suicide risk in patients with major depressive disorder - Yang, Yiyue; Gu, Kaiqi; Li, Jing (Frontiers in Psychiatry, 2024)
Background: Studies have shown that increased inflammatory cytokines are associated with suicide risk, but the relationship between suicide risk and inflammatory cytokines is not clear. This study aimed to investigate the relationship between specific inflammatory markers and suicide risk in patients with MDD.Methods: This is a cross-sectional study. Firstly, we measured and compared psychological characteristics and 10 peripheral inflammatory cytokines in 130 MDD patients and 130 healthy controls(HC). Secondly, MDD patients were divided into 4 groups according to the severity of suicide risk for comparison between groups. Finally, multiple linear regression analysis was used to explore the predictors of suicide risk.We found that the group with higher suicide risk had higher levels of IL-6, CRP, TNF-α, CXCL-2, and IFN-γ, and lower levels of IL-2 and IL-8 (all p<0.01). However, we found no difference in CRP between MIS and LS groups (p=0.337). Regression models were well-fitted. IL-2,IL-8 negatively predicted suicide risk (all p<0.05),IL-6,CRP,TNF-α,CXCL-2, and IFN-γ can positively predict the risk of suicide (all p<0.05).Limitations: This study employed a self-assessment scale.The higher the levels of IL-6, CRP, TNF-α, CXCL-2, and IFN-γ and the lower the levels of IL-2 and IL-8 of MDD patients, the higher the risk of suicide.